2015
DOI: 10.1080/09557571.2015.1008996
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing global imbalances: a perspective on savings and inequality

Abstract: The recent global financial crisis has generated substantial research interest in the relationships among savings, inequality and global imbalances. Our study examines the causes of global imbalances by analysing the relationship between income inequality and economic performance and the relationship between savings imbalances and economic instability. We identify a positive link between savings and inequality whenever savings are allocated through the financial market to investment firms for production. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Policy implications can be derived from the main results obtained in this study. The OECD experience of artificially depressing consumption inequality through financial liberalization shows that this policy can only buy time but may lead to trouble with debt problems and external imbalances later (Kumhof et al, 2012;Sheng, 2015). Surplus countries should not follow such a shortsighted policy and should avoid the accumulation of domestic indebtedness and the risk of financial crises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policy implications can be derived from the main results obtained in this study. The OECD experience of artificially depressing consumption inequality through financial liberalization shows that this policy can only buy time but may lead to trouble with debt problems and external imbalances later (Kumhof et al, 2012;Sheng, 2015). Surplus countries should not follow such a shortsighted policy and should avoid the accumulation of domestic indebtedness and the risk of financial crises.…”
Section: Discussionmentioning
confidence: 99%
“…saving, insurance, and transfers) rather than just household leverage. It is observed that in China, income inequality can be traced closely by consumption inequality (Cai et al, 2010;Ding and He, 2015;Sheng, 2015), however this connection becomes much weaker in the U.S. (Meyer and Sullivan, 2013). As the most representative exampleof a deficit economy, the U.S. obviously has a stronger consumption smoothing ability than China, considered the most representative surplus economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This observation sheds more light on global imbalances and financial crises since this relationship involves more smoothing schemes (e.g., saving, insurance, and transfers), rather than only household leverage. In the case of the United States, consumption inequality is observed to track income inequality loosely (Meyer & Sullivan, 2013) but closely in China (Sheng, 2015). The United States obviously possesses much greater capabilities of consumption smoothing than China, and this has a profound impact on global imbalances (Lardy, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%